Mesenchymal stromal cells isolated from chicken peripheral blood secrete bioactive factors with antimicrobial and regenerative properties - Harman, Rebecca M.; Churchill, Katherine A.; Parmar, Sonia; Van de Walle, Gerlinde R. (Frontiers in Veterinary Science, 2022)
Mesenchymal stromal cells (MSCs) are adult multipotent progenitor cells that have been isolated from various tissue sources of many species, primarily mammals. Generally, these cells proliferate extensively in culture and have been shown to secrete bioactive factors that contribute to healing processes by regulating inflammation, modulating immune responses, inhibiting bacterial growth, and promoting tissue regeneration. The present study reports on the isolation and characterization of MSCs from the peripheral blood (PB) of chickens. Chicken PBMSCs were characterized based on their trilineage differentiation potential and gene and protein expression of MSC-specific cell surface markers. To determine functionality, conditioned medium (CM), which contains all bioactive factors secreted by MSCs, was collected from chicken PBMSCs, and used in in vitro antimicrobial, migration, and angiogenesis assays. Chicken PBMSC CM was found to (i) inhibit the growth of planktonic Staphylococcus aureus (S. aureus), and even more significantly the methicillin-resistant S. aureus (MRSA), (ii) decrease adhesion and promote migration of fibroblasts, and (iii) support endothelial cell tube formation. Collectively, these data indicate that chicken PBMSCs secrete bioactive factors with antimicrobial and regenerative properties, and as such, provide a novel source of cell-based therapies for the poultry industry.